A bibliometric analysis of the cause of sudden unexplained death in forensic medicine: Research trends, hot spots and prospects. (May 2022) - Li, Zehao; Wang, Yuning; Li, Lianjie; He, Henghui; Lin, Lihua; Pan, Meichen; Yang, Tiantong; Liu, Qian
Abstract: To better understand the cause of sudden unexplained death, our group evaluated the scientific results of related studies in a global context. A systematic search of the Web of Science, PubMed and MEDLINE databases identified 2001 studies related to this field published from 1997 to 2020. The studies were analyzed using bibliometric methods, and statistical maps were drawn to explore research trends and research frontiers. Sudden cardiac death and sudden unexpected epilepsy death were the two major causes of sudden unexplained deaths. With the rapid development of high-throughput sequencing technology and bioinformatics in the past 10 years, molecular autopsy has become an effective research method as well as a research hotspot for exploring the cause of sudden unexplained deaths. However, molecular autopsy is underutilized in the investigation of sudden unexpected death in epilepsy. Developing standardized guidelines for diagnostic strategies for the deceased and their families, expanding the screening of mutation spectrum of related diseases, studying the association between variants and diseases in complex genetic diseases, and improving variants interpretation guidelines and disease sequencing databases are future research directions. Highlights: A systematic review of the literature included publication from 1997 to 2020. Bibliometric methods and statistical maps defined research trends and frontiers. Sudden cardiac death and sudden unexpected epilepsy death are the two major causes of sudden unexplained deaths. Molecular autopsy will become an effective research method for exploring sudden unexplained deaths. Molecular autopsy is underutilized in the investigation of sudden unexpected death in epilepsy.